Using sound pressure level and vibration velocity method to determine sound reduction index of lightweight partitions. Issue 2 (June 2019) - Shehap, AM; A Mahmoud, Abd Elfattah; Mohamed, Hatem Kh
Nowadays, lightweight building structures are widely used by the construction industry as a more natural and cost-effective method. The purpose of this study is to compare between sound pressure level and vibration velocity method for sound reduction index determination for single- and double-leaf gypsum board partitions. The sound pressure level method was carried out according to the requirements of ISO 140-3:1997, and the vibration velocity method (V) was carried out according to some criteria of ISO 10848-1:2006. Regarding double-leaf partitions, measurements were carried out with the leaves separated by 5- and 10-cm air gaps. The effect of cavity filling with absorbing materials was studied experimentally. The space between the leaves was filled with Rockwool and polyurethane to illustrate the effect of cavity absorption on the sound reduction index behavior. It was found that there is good agreement between the two methods. Also, cavity filling with a 10-cm absorbing material such as Rockwool increases the sound reduction index at the critical frequency by 7 dB using sound pressure method and 4 dB using vibration velocity method.